Colonial Confessions: an Autoethnography of Writing Criminology in the New South Africa - Dixon, Bill (The British journal of criminology, 2024)
This article is an autoethnographic account of a 20-year engagement with South African criminology. It is written from the perspective of someone from the Global North, a beneficiary of Britain’s colonial past and the present dominance of northern ways of thinking and being. The aim is to encourage other criminologists from a similar background to reflect on their histories and the impact of their work in the present, and to be open to ideas from outside the Euro-American mainstream of the discipline. The evolution of South African criminology, and its gradual adoption of a more southern or decolonial sensibility, is traced in the work of the author and others.